Verification of The Method for Determining Calcium Content in Animal Feed - Syafrinal, Syafrinal; Hafnimardiyanti; Samah, Selfa Dewati; Riani, Pevi; Futeri, Renny; Nurmaliza (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Calcium is one of the essential macromineral elements in animal feed. To ensure that animal feed meets nutritional and safety standards, accurate and validated analytical methods are needed to determine calcium levels, specifically using the ICP-OES (Inductively Coupled Plasma Optical Emission Spectroscopy) technique, which is known for its high sensitivity, enabling the rapid and precise detection of calcium elements at low concentrations. This study aims to verify the method for analyzing calcium content in animal feed, referring to method verification parameters, including linearity, accuracy, precision (repeatability test), limit of detection (LoD), method detection limit (MDL), and limit of Quantitation (LOQ). The verification process was conducted using calcium standard solutions at various concentrations and analysis of animal feed samples according to SNI 3148.2:2009 using Inductively Coupled Plasma (ICP-OES) with a linearity test parameter coefficient of correlation (r) value of 0.9991, precision with a % RSD value of 2.18%, accuracy (recovery) reaches 90-99%, with a detection limit (LoD) of 0.0745 mg/L and a Limit of Quantitation (LoQ) of 0.9060 mg/L, all of which meet the acceptance criteria set by AOAC. These results prove that the ICP-OES technique is suitable for use as a test method for determining the calcium content in animal feed, can be adopted as a standardized routine procedure.